Opinion: From 'Look East' and 'Act East', India must 'think big' and 'act big' - Ajmani, Manmeet Singh; Roy, Devesh (2018)
“We believe, that trade facilitation and enhanced connectivity can help India realise its untapped export potential with ASEAN. Yet, the full realisation of the potential would only happen when India ups the game on industrial products and technology.”